Możliwość oczyszczania ścieków z ich wykorzystaniem do lokalnej retencji na przykładzie gminy Kamieniec = Posibility of clean-up treatment of sewage with their utilization for local retention based on example of Kamieniec district - Halicki, Wojciech; Pniewska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Activities which were giving ride to increase of the acreage of land production has caused the environment forfeited the natural ability for water retention. The article shows the way of formation the areas of water retention with simultaneous resolving problems of sewage management basing on the one of polish districts.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)